Structural optimization of photoacoustic transducer with PDMS/CSNPs nanocomposite for fatigue crack detection using laser-induced nonlinear surface waves - Zhijun Yao; Yehai Li; Gaolong Lv; Dan Chen; Jian Yang; Shifeng Guo (Materials & Design, 2024)
Laser ultrasonics is a promising non-contact inspection technique but faces challenges of low signal-to-noise and low amplitude under non-destructive thermoelastic regime. In this paper, a laser ultrasonic surface acoustic wave (SAW) modulation method and photoacoustic transducer (PAT) are proposed and combined with nonlinear wave mixing technique to inspect microscale fatigue crack. PATs comprised of candle soot nanoparticles and polydimethylsiloxane are systematically optimized and combined with a line-arrayed laser source to generate desired high-amplitude and pure fundamental SAWs. Two modulated SAWs with frequencies of 2.1 and 2.9 MHz are excited on a fatigued aluminum plate to generate nonlinear mixed components, and the ultrasonic responses over the fatigue crack regions are acquired with a scanning laser Doppler vibrometer. The localization of fatigue crack with microscale is eventually achieved by mapping the nonlinear parameter of the mixed components, which proves it a reliable and non-destructive technique to inspect the fatigue crack.